Factors Influencing Foreign Direct Investment in the Manufacturing Sector of Malaysia - Yusop, Zulkornain (1992)
This study is meant to identify local(country-related) factors that affect foreign direct investment (FDI) in the manufacturing sector of Malaysia. FDI in Malaysia was concentrated in the agricultural and extractive industries until the early post-independent period when efforts to diversify the country's economy were initiated. Generally, industrialization has brought several positive effects however, it also features a few weaknesses such as narrow manufacturing base and manufactured exports and under utilization of local resources. The different rates of investment across the various manufacturing industries in the country can be associated with the pattern of FDI which is concentrated in certain industries such as electrical and textile. Therefore, it is important to conduct a study on factors affecting FDI in Malaysia so that policy-makers can hopefully benefit from the findings of the study in making the appropriate policies to improve the distribution of FDI across the manufacturing industries. Previous studies show that FDI activities can be explained by theory of comparative advantage, industrial organization as well as investment theory. To determine the factors influencing FDI in the Malaysian manufacturing, both quantitative and qualitative analyses were conducted. In the quantitative analysis, gross national product(GNP),level of external reserve (lagged one year), interest rate, manufacturing output/GNP, current profit of foreign controlled manufacturing companies and total asset of local financial systems how significant positive relationship with FDI while public investment rate shows significant negative relationship. The qualitative analysis concludes that economic and social stability; freedom of repatriation; avail ability of efficient labour force; existence of physical infrastructures;efficiency of financial institutions; tariff and trade protection; currency stability; market avail ability; and public sector efficiency are among the roost important determinants of FDI.